DIALEKTIKA TRADISI DAN SYARIAT: PRAKTIK KHITBAH TERBALIK DI KABUPATEN LAMONGAN DALAM TINJAUAN HUKUM ISLAM - In'am Awaluddin, Ahmad; Syahrial Ramadhan, Muhammad Dhiya'Ulhaq (LPPM STAI Muhammadiyah Probolinggo, 2025)
The tradition of reverse khitbah in Lamongan Regency, where women take the initiative to propose to men, is a unique phenomenon that has been practiced for generations since the 17th century. This study analyzes the legitimacy of these traditions through the theoretical framework of 'urf and maqashid sharia. Using a literature research method, this study synthesizes the findings of previous research in Paciran, Modo, Mantup, and Mayong Village, Karangbinangun District, and evaluates them against primary Islamic sources. The results of the study show that reverse khitbah has normative legitimacy in the hadiths of the Prophet and the practices of the Companions, without any explicit prohibition in Islamic law. From the perspective of the theory of 'urf, this tradition is included in 'urf sahih (a valid custom) because it meets four criteria: it does not contradict nash qath'i, brings benefits without harm, has been in practice consistently for more than three centuries, and is a manifestation of the rules of taghayyur al-ahkam bi taghayyur al-azman wa al-amkan. Through the methodology of superstition by adopting the contemporary maqashid approach of Jasser Auda, this tradition is in line with the goals of the protection of religion (hifzh al-din), heredity (hifzh al-nasl), and dignity (hifzh al-karamah). This research contributes theoretically by offering an integrative analytical framework that combines contemporary 'urf theory, taghayyur rules, and maqashid, and practically provides academic legitimacy for local traditions and perspectives for policymakers on the flexibility of Islamic law in local contexts.